2018
DOI: 10.1002/bem.22124
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor effect of static and extremely low frequency magnetic fields against nephroblastoma and neuroblastoma

Abstract: Certain magnetic fields (MF) have potential therapeutic antitumor effect whereas the underlying mechanism remains undefined. In this study, a well-characterized MF was applied to two common childhood malignancies, nephroblastoma and neuroblastoma. This MF has a time-averaged total intensity of 5.1 militesla (mT), and was generated as a superimposition of a static and an extremely low frequency (ELF) MF in 50 Hertz (Hz). In nephroblastoma and neuroblastoma cell lines including G401, CHLA255, and N2a, after MF e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
1
18
0
2
Order By: Relevance
“…Previously in our lab, G401 nephroblastoma xenograft has been successfully established in nude mice. The tumor was fairly resistant to DDP, and MF sensitized the tumor to DDP treatment [17]. In this study, occurrence of DNA damage and activation of repair has also been confirmed in tumor xenografts.…”
Section: Agingsupporting
confidence: 67%
See 4 more Smart Citations
“…Previously in our lab, G401 nephroblastoma xenograft has been successfully established in nude mice. The tumor was fairly resistant to DDP, and MF sensitized the tumor to DDP treatment [17]. In this study, occurrence of DNA damage and activation of repair has also been confirmed in tumor xenografts.…”
Section: Agingsupporting
confidence: 67%
“…In this study, a previously reported tumor suppressing field [17] has been further shown to selectively inhibit several types of cancer cells. Similarly in another study, a 50 Hz field with a flux density of 1 mT induced apoptosis in a transformed human squamous cell carcinoma line, but not in a non-transformed human amniotic fluid cell line [11].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations